KONSTRUKSI REALITAS HIJAB PADA WANITA MUSLIMAH DALAM FILM “99 CAHAYA DI LANGIT EROPA” - Rizka Fitri; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Hijab became a way of life for the society. By the increasing spread of hijab users the world fashion industry, this situation looks natural and elegant. Style with modern hijab is now constructed by mass media. In accordance with Islamic themes in film 99 Cahaya di Langit Eropa gave an overview of Islamic lifestyle on society. But in this film there is a difference from other Islamic-themed films. In this film forming new thinking that a Muslim woman could looks beautiful by using the makeup and dress up with various models of clothes are a trend in public area but still wear hijab. So this study was aimed to determine the construction of hijab reality on Muslim women in film 99 Cahaya di Langit Eropa (part 1 and part 2) and the viewpoint from the viewers.This study uses descriptive qualitative method which were analyze through by semiotics of Charles Sanders Pierce. Data collection techniques has been used observation of audio/dialog and visual display in the film 99 Cahaya di Langit Eropa (part 1 and part 2), documentation, and interviews using purposive sampling technique.The results of this research indicated that there were some construction of reality in the film 99 Cahaya di Langit Eropa (part 1 and part 2). First, Hijab was using as the identity of Muslim women, hijab can ennoble of Muslim women, hijab can prevent women from male disorder which are unresponsible, hijab able to strengthen of social control, hijab realize women have a good character, and women can look fashionable while still wearing the hijab. Second, the viewpoint from audience about the film is the film depicts the hijab that doesn’t comply with Islamic law, that supposed to be become simple and inconspicuous.Key words : Construction of Reality, Hijab, Muslim Woman, Film, Docu-Drama